New records of Pontocaris affinis affinis (Alcock, 1901) and Pontocaris propensalata Spence Bate, 1888 (Crustacea: Decapoda: Crangonidae) from Quilon bank of Southeastern Arabian Sea - Purushothaman, P.; Chakraborty, Rekha Devi; Kuberan, G.; Maheswarudu, G. (Zootaxa, 2018)
This paper reports on two crangonid shrimps, Pontocaris affinis affinis and Pontocaris propensalata from Southeastern Arabian Sea. Continuous surveys in the Quilon bank yielded two new records of Pontocaris, which were found on the continental slope at 250–300 m depth. A 4.1% of genetic divergence between the 16S DNA sequences of the two species was noticed.